Loin de la Syrie, loin de la Révolution - Léo Fourn (Revue des Mondes Musulmans et de la Méditerranée)
Absence is inherent to exile. Syrian activists who fled the brutal crackdown and the war share with all exiles the experience of absence. We propose to examine absence experienced through the prism of political commitment in which geographical distances are exacerbated by distance from the cause in favor of the “Syrian revolution”. Presently settled in France, these activists experience many kinds of suffering related to exile. They try to alleviate it by maintaining links with the ongoing protests. The evolution of the conflict however, and protracted delays lead them to resignation, and to an acceptance of absence and a distancing from their commitment to the cause. This article thus examines the relations between exile and political commitment.